2012
DOI: 10.1111/j.1477-2574.2012.00457.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalences of and risk factors for biliary stones and gallbladder polyps in a large Chinese population

Abstract: Objectives:  This study aimed to identify the prevalences of and risk factors associated with the development of gallbladder stones and polyps in a large Chinese population. Methods:  Prevalences of and risk factors for biliary stones and gallbladder polyps were retrospectively investigated among subjects who underwent a general check‐up at the Health Screening Centres of Peking Union Medical College Hospital and Beijing Charity Hospital between January 2007 and June 2010. Results:  A total of 60 064 people we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
49
2
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 38 publications
5
49
2
2
Order By: Relevance
“…Age, sex and heredity have been mentioned as factors related to gallstone disease. 7,17,[23][24][25][26][27][28][29] Similar to the previous studies, our data…”
Section: Risk Factors For Large Gallstones and Multiple Stonessupporting
confidence: 90%
See 1 more Smart Citation
“…Age, sex and heredity have been mentioned as factors related to gallstone disease. 7,17,[23][24][25][26][27][28][29] Similar to the previous studies, our data…”
Section: Risk Factors For Large Gallstones and Multiple Stonessupporting
confidence: 90%
“…Female sex is an evident risk factor for gallstones in Europe and North America, but is not related to its prevalence in the East Asian population. 7,17,19,20,[23][24][25][26] Additionally, data from China showed a high prevalence of gallstones in women in the Uyghur group but in not the Han Chinese group. 7 In the current study, we found no correlation between sex and gallstones (6.22% in men vs 7.31% in women, P = 0.173).…”
Section: Risk Factors For Large Gallstones and Multiple Stonesmentioning
confidence: 99%
“…Numerous of studies [4,5,41] have confirmed that gallstone are the main cause of GBC. We found that obesity was not only strongly associated with gallstones [42] but also had an increased frequency of gallstones [43].…”
Section: Discussionmentioning
confidence: 99%
“…Appendicitis continues to be the first cause and could not be ruled out initially in this case. Cholelithiasis is another possibility, since obesity is associated with a 25% increased risk of this pathology [7]. Pancreatitis would be the third possibility, given its high rates of occurrence in obese patients due to the existence of biliary stones.…”
Section: Discussionmentioning
confidence: 99%